Innovative STEAM Learning: Creating Engaging Colloid Material Videos for High School Students Using CapCut - Pinandhita, Boy; Fuldiaratman, Fuldiaratman; Sanova, Aulia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to develop STEAM-based learning videos using the CapCut application on Colloid material at the high school level. Methodology: This study is a development research using the Lee & Owens development model. The research instruments used were interview guidelines and questionnaires. The development products were validated by media experts and material experts, practitioner assessments were carried out by teachers and then tested in small groups. The data analysis techniques used were qualitative data analysis (comments and suggestions) and quantitative data analysis (average score of answers and percentage of questionnaires). Main Findings: The results of this study were obtained from material experts and media experts with an average score of 4.58 and 4.75 in the Very Eligible category. Furthermore, a practitioner’s assessment by chemistry teachers was obtained with an average score of 4.8 (very feasible), and received a very good response from students with a percentage of 93.5%. Novelty/Originality of this study: This study introduces a novel approach by integrating STEAM principles into the development of learning videos on colloid materials, leveraging the CapCut application to enhance creativity and interactivity in high school education. Unlike traditional teaching methods, this research combines technology-driven video editing with STEAM-based learning to foster critical thinking, collaboration, and practical application of scientific concepts in an engaging multimedia format.